2013
DOI: 10.5539/res.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Aging with Diabetes: Sense of Coherence and Satisfaction with Life in European Older Adults with Type 2 Diabetes

Abstract: Objectives: The population's increased longevity is leading to a worldwide concern about older adults' well-being and about the incidence of chronic diseases such as diabetes. The present research intends to: (a) determine significant differences among three groups of older adults with diverse diabetes diagnosis, namely, participants with only type 2 diabetes, participants with diabetes and other chronic diseases and the remaining without any chronic disease, regarding the satisfaction with life (SWL) and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The results of the present study showed that the distance empowerment program affected the sense of coherence of the multiple sclerosis patients participating in the study and the sense of coherence of patients in the intervention group signi cantly improved after the intervention. This result is in line with the ndings of Hourzad [23], Mousavi Nasab [24], Stern [25], Mirhashmi[26], von Humboldt [27], Pourfried[28], and Odajima [29]. In Hourzad et al's study, retired elderly people with chronic diseases participated in a ve-stage self-management empowerment model.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the present study showed that the distance empowerment program affected the sense of coherence of the multiple sclerosis patients participating in the study and the sense of coherence of patients in the intervention group signi cantly improved after the intervention. This result is in line with the ndings of Hourzad [23], Mousavi Nasab [24], Stern [25], Mirhashmi[26], von Humboldt [27], Pourfried[28], and Odajima [29]. In Hourzad et al's study, retired elderly people with chronic diseases participated in a ve-stage self-management empowerment model.…”
Section: Discussionsupporting
confidence: 74%
“…Chronic diseases such as diabetes and the presence of various diseases affect people's life satisfaction and sense of coherence in different ways. This study showed the importance of life satisfaction and a sense of coherence for elderly people, especially when there is diabetes and their relationship in the context of healthy aging in older populations [27].…”
Section: Discussionmentioning
confidence: 72%
“…These outcomes are corroborated by previous studies by Humboldt, Leal, Santos & Niculescu (2013), on Aging with Diabetes: Sense of Coherence and Satisfaction with Life in European Older Adults with Type 2 Diabetes that underline that presence of diabetes influences satisfaction with life(SWL) and sense of coherence (SOC), only diabetes' group had lowest SOC and SWL scores , this group also showed an association between SOC and SWL scores . In the 'without diabetes' and 'with diabetes and other' groups no correlation was found between SOC and SWL scores, In a similar study by Rubin and Peyrot (1999) , it has been found that better glycemic control is related with better quality of life, no matter how intensive treatment is given , any kind of complication in diabetes had a detrimental effect on quality of life , similarly when patient's health status is improved and their perceived ability to control their disease was increased it showed improved quality of life in them.…”
supporting
confidence: 79%
“…[2,10] there is still very little data to characterize the daily life of persons with diabetes or analyze their satisfaction with life. [12][13][14] We also found an interesting study that researched the level of knowledge that social scientists have about diabetes (whether diabetes is treatable, is diabetes characterized by high blood sugar levels, what are the symptoms of diabetes). The prerequisite was that professionals who work in areas related to social sciences, health, sociology, demography, and psychology should be "agents of change" by increasing the society's awareness with their research, thus improving attitudes towards people with diabetes.…”
Section: Introductionmentioning
confidence: 92%